Optical code division multiple access : - Kitayama, Ken-Ichi
"A comprehensive guide to optical fiber communications, from the basic principles to the latest developments in OCDMA for Next-Generation Fiber-to-the-Home (FTTH) systems. Part I starts off with the fundamentals of light propagation in optical fibers, including multiple access protocols, and their enabling techniques. Part II is dedicated to the practical perspectives of Next-Generation Fiber-to-the-Home (FTTH) technology. It covers the key building blocks of OCDMA, devices such as optical encoders and decoders, signal impairments due to noise, and data confidentiality, a unique property of OCDMA. This is followed by hybrid system architectures with TDM and WDM and practical aspects such as system cost, energy efficiency and long-reach PONs. Featuring the latest research, with cutting-edge coverage of system design, optical implementations, and experimental demonstrations in test beds, this text is ideal for students, researchers and practitioners in the industry seeking to obtain an up-to-date understanding of optical communication networks"--